Measurement of specific IgE antibodies to Ses i 1 improves the diagnosis of sesame allergy. Issue 1 (January 2016) - Maruyama, N.; Nakagawa, T.; Ito, K.; Cabanos, C.; Borres, M. P.; Movérare, R.; Tanaka, A.; Sato, S.; Ebisawa, M.
Summary: Background: The number of reported cases of allergic reactions to sesame seeds ( Sesamum indicum ) has increased significantly. The specific IgE tests and skin prick tests presently available for diagnosis of sesame allergy are all based on crude sesame extract and are limited by their low clinical specificity. Thus, oral food challenge (OFC) is still the gold standard in the diagnosis. Objective: The aim was to identify the allergen components useful to diagnose sesame‐allergic children with the goal to reduce the number of OFCs needed. Methods: Ninety‐two sesame‐sensitized children were consecutively enrolled and diagnosed based on OFC or convincing history. Specific IgE to purified native 11S globulin (nSes i 11S), 7S globulin (nSes i 7S), 2S albumin (nSes i 2S), and two recombinant 2S albumins (rSes i 1 and rSes i 2) was measured by ELISA and/or ImmunoCAP (rSes i 1/streptavidin application). Results: Based on area under curve (AUC) values from receiver operating characteristic (ROC) analysis, rSes i 1 was shown to have the best diagnostic performance of the allergen components in ELISA. The experimental rSes i 1 ImmunoCAP test had larger AUC (0.891; 95% CI, 0.826–0.955) compared to the commercially available sesame ImmunoCAP (0.697; 95% CI, 0.589–0.805). The clinical sensitivity and specificity for the rSes i 1 ImmunoCAP test at optimal cut‐off (3.96 kUA /L) were 86.1% and 85.7%, respectively. Conclusion and Clinical Relevance: Sensitization to Ses i 1 is strongly associated with clinical sesame allergy. Measurement of specific IgE to rSes i 1 could reduce the numbers of OFCs needed.